Coinfection of Leptospirosis with Scrub Typhus: A Case Report - Surontee, Rayeed Anan; Hoque, Mohammad Mahfuzul; Tasneem, Tahsina; Fariduzzaman, Md; Hasan, Md Mehedi; Bari, Md Shafiqul (Journal of Medicine, 2024)
Leptospirosis and scrub typhus are common zoontic illnesses in tropical countries. Leptospira, a spirochaete, can cause leptospirosis when a patient comes in contact with contaminated water. Following a period of bacteraemic illness, leptospirosis may progress to a more severe form. Weil’s disease is a severe form of leptospirosis characterised by jaundice, haemorrhage and acute kidney injury. Scrub typhus, a rickettsial disease, common in South-East Asia is caused by Orientia tsutsugamushi occurs due to bite of Trombicula mite. An eschar forms at the site of the bite. Here we present a case of a 60-year-old gentleman, hailing from Savar who was diagnosed as a case of coinfection of scrub typhus and leptospirosis. Patient presented with an eschar, high grade fever and features of Weil’s disease. He didn’t initially respond to Ceftriaxone and then Doxycycline was added after which he became afebrile. J MEDICINE 2024; 25: 187-190